artikel Keuangan Berkelanjutan dan Integrasi ESG dalam Perbankan Syariah: Jalan Menuju Investasi Halal di 2024 : Jalan Menuju Investasi Halal 2024 - Hamidah Wakid; Saiful Bakhri (Cashless : Journal of Sharia Finance and Banking, 2024)
Sustainable finance has become a key focus in the development of the global financial sector. This concept integrates three main pillars: Environmental, Social, and Governance (ESG), in investment decisions and the operations of financial institutions. In the context of Islamic banking, the ESG concept can be applied by emphasizing Sharia principles that include justice, transparency, and positive social impact. This journal aims to analyze the implementation of ESG in Islamic banking and how it can contribute to the development of sustainable halal investments, as well as the challenges and opportunities in 2024. The research shows that integrating ESG in Islamic banking not only strengthens reputation and social value, but also paves the way for the development of more inclusive and environmentally friendly halal investment products.